2(14x+27y)-4(23x-7y)=236

Simple and best practice solution for 2(14x+27y)-4(23x-7y)=236 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(14x+27y)-4(23x-7y)=236 equation:


Simplifying
2(14x + 27y) + -4(23x + -7y) = 236
(14x * 2 + 27y * 2) + -4(23x + -7y) = 236
(28x + 54y) + -4(23x + -7y) = 236
28x + 54y + (23x * -4 + -7y * -4) = 236
28x + 54y + (-92x + 28y) = 236

Reorder the terms:
28x + -92x + 54y + 28y = 236

Combine like terms: 28x + -92x = -64x
-64x + 54y + 28y = 236

Combine like terms: 54y + 28y = 82y
-64x + 82y = 236

Solving
-64x + 82y = 236

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-82y' to each side of the equation.
-64x + 82y + -82y = 236 + -82y

Combine like terms: 82y + -82y = 0
-64x + 0 = 236 + -82y
-64x = 236 + -82y

Divide each side by '-64'.
x = -3.6875 + 1.28125y

Simplifying
x = -3.6875 + 1.28125y

See similar equations:

| 3(x+8)=6x+2-3x+22 | | a-3/2a3:a-1/a-2 | | 1/5y-3=1 | | 6y^2-14y+8=0 | | 2x+3y-x-[8+1]= | | w/3-9=20 | | 6x+3x+12(4x+3)=x | | 15-2w=5 | | 40-5*7+11= | | 30.25(x)=59.5 | | Y/10-8=-16 | | 7x+4y=8x | | N/5-1=-2 | | 10=3m+7 | | 2=x^2-5x | | 13/7(1/4) | | 4z^2-24z+30=0 | | 12x+21=10x+26 | | 1+1-2-5+54*X= | | 2cosx+4= | | Y/3-12=-2 | | .5n+3= | | .5+3= | | d+1.7=-1.3 | | f=epd*e | | (6xy^2+5x^2y-2y^2)-(-3x^2y-7xy^2+y^2)= | | 3(4x-17)=5 | | -12k^2+k+20=0 | | 25x^3-10x^2-3x-4=0 | | X+3=2z | | 4x+my=ny-3 | | .3n=6 |

Equations solver categories